Antiviral therapy and outcomes of patients with pneumonia caused by influenza A pandemic (H1N1) virus. - Shi-gui Yang; Bin Cao; Li-rong Liang; Xiao-li Li; Yong-hong Xiao; Zhi-xin Cao; Hong-yu Jia; Hong-jie Yu; Zhen Xu; Li Gu; Yi-da Yang; Yu Chen; et al. (PLoS ONE, 2012)
BACKGROUND: There is limited data on the clinical outcome of patients with pandemic H1N1 (pH1N1) pneumonia who received oseltamivir treatment, especially when the treatment was administered more than 48 hours after symptom onset. METHODS: During the pandemic in 2009, a cohort of pH1N1 influenza pneumonia was built in China, and their clinical information was collected systematically, and analyzed with Cox models. RESULTS: 920 adults and 541 children with pneumonia who didn't receive corticosteroids were analyzed. In-hospital mortality was higher in adults who did not receive antiviral therapy (18.2%) than those with who received oseltamivir ≤ 2 days (2.9%), between 2-5 days (4.6%) and >5 days after illness onset (4.9%), p<0.01. A similar trend was observed in pediatric patients. Cox regression showed that at 60 days after symptoms onset, 11 patients (10.8%) who did not receive antivirals died versus 4 (1.8%), 18 (3.3%), and 23 (3.7%) patients whose oseltamivir treatment was started ≤ 2 days, between 2-5 days, and >5 days, respectively. For males patients, aged ≥ 14 years and baseline PaO(2)/FiO(2)<200, oseltamivir administration reduced the mortality risk by 92.1%, 88% and 83.5%, respectively. Higher doses of oseltamivir (>3.8 mg/kg/d) did not improve clinical outcome (mortality, higher dose 2.5% vs standard dose 2.8%, p>0.05). CONCLUSIONS: Antiviral therapy might reduce mortality of patients with pH1N1 pneumonia, even when initiated more than 48 hours after onset of illness. Greater protective effects might be in males, patients aged 14-60 years, and patients with PaO(2)/FiO(2)<200.